UV protection test of the ethanol fraction of papaya cream (Carica papaya L.) added with titanium dioxide - Definingsih Yuliastuti; Wahyunita Yulia Sari; Mustikawati Mustikawati (Universitas Ahmad Dahlan, 2020)
Cream containing papaya fruit (10% of the 70% ethanol fraction) has been reported to effectively protect skins from ultraviolet (UV) light, though with a minimum protection ability. This study was aimed to determine the effects of adding titanium dioxide to sunscreen composed of 70% ethanol fraction of papaya flesh on the cream effectiveness, as measured by SPF values and physical properties. The ethanol fraction was obtained by fractionating the 70% ethanol extract of papaya fruit using n-hexane and ethyl acetate. Then, it was added with three different concentrations of titanium dioxide, namely, 1% (FI), 3% (FII), and 5% (FIII), to form cream preparations. These sunscreens were tested for their effectiveness in UV protection by in vitro spectrophotometry and based on the resultant SPFs. Based on the results of the study, the cream prepared with no titanium dioxide had SPF= 1.1283, while the SPFs of cream preparations added with 1%, 3%, and 5% titanium dioxide were 2.0572, 2.5708, and 2.8832, respectively. At these three concentrations, titanium dioxide increased the SPFs by 45%, 56%, and 61%, respectively. The cream preparations were found to have excellent physical properties. Based on the results of the statistical Kruskal-Wallis test, there are significant differences (p<0.05) between FI, FII, and FIII.